Microglia and Synapse: Interactions in Health and Neurodegeneration - Zuzana Šišková; Marie-Ève Tremblay (Neural Plasticity)
A series of discoveries spanning for the last few years has challenged our view of microglial function, the main form of immune defense in the brain. The surveillance of neuronal circuits executed by each microglial cell overseeing its territory occurs in the form of regular, dynamic interactions. Microglial contacts with individual neuronal compartments, such as dendritic spines and axonal terminals, ensure that redundant or dysfunctional elements are recognized and eliminated from the brain. Microglia take on a new shape that is large and amoeboid when a threat to brain integrity is detected. In this defensive form, they migrate to the endangered sites, where they help to minimize the extent of the brain insult. However, in neurodegenerative diseases that are associated with misfolding and aggregation of synaptic proteins, these vital defensive functions appear to be compromised. Many microglial functions, such as phagocytosis, might be overwhelmed during exposure to the abnormal levels of misfolded proteins in their proximity. This might prevent them from attending to their normal duties, such as the stripping of degenerating synaptic terminals, before neuronal function is irreparably impaired. In these conditions microglia become chronically activated and appear to take on new, destructive roles by direct or indirect inflammatory attack.